The Role of Self Awareness in Improving the Adjustment of Santri at Tsurayya Islamic Boarding School - Ismail, Annisa; Puspitasari, Fiolita Indah; Solichatun, Yulia; Rahayu, Iin Tri (Proceedings Conference Psychology and Flourishing Humanity, 2025)
Since ancient times, Islamic boarding schools have been used as religious-based educational institutions which have their own characteristics so that they have prominent differences from formal educational institutions in general. In focusing on forming piety, self-awareness is needed. This is the ability to know oneself and understand one's tendencies in acting, to understand feelings, and even to understand one's situation and condition well. The aim of this research is to understand the role of self-awareness and its relationship with the students' adjustment at Tsurayya Islamic Boarding School. The research method used is qualitative method. The approachment used is a case study. The results of the research showed that 1) Self-awareness plays an important role in training awareness and contrition so that the students's character formed which could practice the values of Islamic faith based on the Qur'an and Sunnah as well as independent individuals expected from Tsurayya Islamic Boarding School. 2) Self-awareness allows students to recognize emotions so they can control their emotional reactions. This could help students adjust well. 3) Students who have good self-awareness tend to find it easier and more open to adapt. So, the implication is that students who have self-awareness make it possible to carry out better self-development, students carry out effective emotional management and are able to learn the knowledge they have acquired so that it can be used to overcome the problems they face.